A methodological support to set up multidisciplinary group practices in Southeastern France. (13th November 2019) - Douchement, O; Dumesnil, H; Dagnet, L; Saugeron, B; Sonnier, P; Verger, P; Guagliardo, V
Abstract: Issue/Problem: Despite high medical densities in Southeastern France, access to prevention and care is difficult in some territories due to a lack of health professionals. The Regional Council supports multidisciplinary group practices (MGP) to improve primary care access and quality. When developing them, health professionals have to propose a health project addressing population health needs in the area. Description of the problem: Two complementary resource centres -the Southeastern Regional Health Observatory and the Regional Committee for Health Education- collaborate to provide support to health professionals in the creation of MGP. The process includes a territorial assessment based on quantitative indicators about various environmental and socio-economic determinants, morbidity, mortality, and health-seeking behaviours. Stakeholders then discuss the results of this assessment in order to confront it to their experiences, identify priorities and design the health project: it defines the forms according to which professionals will work together and set specific objectives and activities to cover main public health needs in the corresponding territory. Results: Since 2011, our methodological support has benefited 45 MGP projects: 19 were successful, 13 are still in progress and 13 projects were not completed. It helped decision-makers in the identification of priority territories in terms of prevention and care; it also presented outlooks of the current and coming health needs of various areas. Lessons: Levers to the MGP setting up have been identified: a project is more successful when it is initiated by health professionals supported by local authorities, and up for discussion. On the contrary, preconceived ideas about the MGP project complicate the assessment's appropriation. Key messages: Taking into account the results of the assessment helps to propose MGP projects that better match population needs. It also improves collective knowledge of public health issues between health professionals and various local stakeholders.